Development of a diagnostic real time pcr assay for molecular detection and characterization of mycoplasma gallisepticum - Yasmin, Farhana (2013)
Mycoplasma gallisepticum (MG) causes chronic respiratory disease leading to huge economic losses to poultry industry worldwide. Early and efficient detection is therefore crucial in reducing the loss sustained by poultry farmers and poultry industry at large. This study was carried out to develop SYBR green Real Time Polymerase Chain Reaction (PCR) for the detection of MG and to perform molecular characterization of local MG strains based on gene targeted sequencing (GTS) analysis. A Real Time PCR assay was developed using primer specific to gapA gene. The primer was able to amplify the expected DNA fragment of 505 bp. The assay was found to be specific and highly sensitive in detecting MG as indicated by its ability to detect MG at early cycle of amplification with 26.05 Cq value in comparison with other avian Mycoplasma species as well as the ability of detecting 260ng/μl to 26pg/μl of DNA template. A total of 300 swab samples were collected from different poultry farms (layer breeder, broiler breeder, broiler chicken and village chicken) in Peninsular Malaysia and tested for the presence of MG using the developed PCR assay. Of the total number of samples tested, 31% (94/300) were found to be positive for MG, thus, indicating high prevalence of MG infection in many distinct geographical areas of the country. Although,farmers vaccinate and treat the chickens against MG in Malaysia, the results of the present study suggest that the control of MG might not be efficient. In order to gain further observation on the molecular characteristics of Malaysian MG strains detected in this study, selected gene target specific sequences to MG, hemagglutinin protein A gene (pMGA) and phase variable putative adhesion protein A gene (pvpA), were amplified from positive MG samples using conventional polymerase chain reaction. A total of 25 MG positive field samples out of 94 MG samples were sequenced with the primer targeting the pMGA and also pvpA gene. The sequencing and phylogenetic analysis were conducted using bioinformatics software (Bioedit and MEGA 5 Software) and genetic variation patterns were evaluated based on partial nucleotide sequencing of the pMGA and pvpA genes. In case of pMGA partial nucleotide sequences, all 25 local field strains showed similar gene size pattern with pathogenic reference strain, MGS6 and pathogenic vaccine strain, MG F which is different from the PCR product size of less pathogenic vaccine strain,TS 11. In the same way, pvpA partial nucleotide sequences of MG local strains showed that 20 out of 25 local strains possess similar gene size pattern with MG F, which is different from MGS6 and TS 11. From the phylogenetic analysis of pMGA and pvpA partial nucleotide sequences, it was found that local (Malaysia) MG strains are different from the strains reported in other countries (Australia, USA, Iran, Israel, China and Russia).In conclusion, this study successfully developed a specific and sensitive real time PCR assay for the rapid detection of MG compared to conventional PCR method. Although the cost to carry out real time PCR is more expensive, it is more specific, sensitive, and more rapid for detection of MG as compared with conventional PCR. With more research, the time and cost factors can be improved. This method gave result within an hour but conventional PCR took 3 hrs excluding post PCR processing. Based on the pMGA and pvpA partial nucleotide sequence analysis and phylogenetic tree it was shown that local MG strains were different from strains reported in other countries (Australia,USA, Iran, Israel, China and Russia).